Indirect exporters and importers - Marco Grazzi; Chiara Tomasi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
This paper analyses the relation between firms' productivity and the different modes of participation to international trade. In particular, we account for the > possibility that firms can not only export their products, but also internationally source their inputs, either directly or indirectly. Using a cross section of firm-level data for several advanced and developing economies, the study confirms the productivity-sorting prediction according to which domestic firms are less efficient than those resorting to an export intermediary, while the latter are less productive than producers which export directly. We show that the same sorting exists also on the import side. Finally, we investigate the effects of source country characteristics on the sorting of firms into different modes of international trade. >
Keywords: F14; D22; L22; 330